1 PENGARUH KINERJA PEGAWAI TERHADAP KUALITAS PELAYANAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MINAHASA. - WOWOR, FRAMI; RORONG, ARIE; MAMBO, RULLY (Sam Ratulangi University, 2019)
The purpose of this study is to find out how much influence the performance of employees on service quality with quantitative research using instruments, validity, and reliability tests, while data analysis using simple regression analysis techniques. From the problems that occur due to research on the performance of employees in the Minahasa regency regional government, especially at the Minahasa District Population and Civil Disability Office, it seems that they are still less effective and efficient. This can be seen from the performance of each employee that is still not maximal in completing the functions and tasks that have been determined by the local government agencies. This has an impact on the lack of employee performance.This certainly impacts on the quality of services provided to people who have government administrative affairs at the Minahasa District Civil Registry Service office this phenomenon is evidenced by the various highlights of employee performance in providing services as described above.From the observations carried out by the author at the office of the Minahasa District Civil Registry Service, it shows that employee performance is felt to be very far from the expectations of the people who are dealing with the office, causing unrest and unfavorable public opinion. The lack of facilities and infrastructure is another problem possessed by the Minahas Regency Civil Registry office and the lack of officers who oversee employee performance results has made this agency seem to work as well as possible without the process of accountability in accordance with the principles of centralization and decentralization.Keywords: Employee Performance, Service Quality